ENHANCEMENT IN THE YIELD OF DIOSGENIN BY NITROGEN AND SULPHUR NUTRIENTS IN TRIBULUS TERRESTRIS L. - SANJEEV KUMAR; ALKA NARULA; P.S.SRIVASTAVA (International Journal of Pharma and Bio Sciences, 2016)
Field experiments were conducted to study the effect of nitrogen and sulphur nutrients on growth performance of a medicinal plant, Tribulus terrestris and yield of diosgenin. Application of urea at the rate of 60, 100 and 150 kg N ha-1 significantly enhanced the growth of plants and also the yield of secondary metabolite, diosgenin. Combined effect of Sulphur x Nitrogen (SxN) along with neem cake proved better than nitrogen alone. Our results indicate that specific and balanced application of inorganic, and/or organic nutrients can be effective in increasing the productivity of medicinal plants.